Microfoundational programs - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2010)
The substantial questions of macroeconomics itself are very old, going back to the origins of economics itself. But professional self-consciousness of the distinction between macroeconomics and microeconomics dates only to the 1930s. The distinction was drawn quite independently of Keynes, yet Keynes's General Theory led to its widespread adoption. The question of the relationship of microeconomics to macroeconomics encapsulated in the question of whether macroeconomics requires microfoundations was not raised for the first time in the 1960s or '70s, as is sometimes thought, but goes back to the very foundations of macroeconomics. There are in fact at least three microfoundational programs: a Marshallian program with its roots directly in Keynes's own theorizing in the General Theory; a fixed-price general-equilibrium theory, which includes some work of Patinkin, Clower, and Barro and Grossman; and the more recent representative-agent microfoundations, starting with Lucas and the new classicals in the early 1970s. This paper will document the development of each of these microfoundational programs and their interrelationship, especially in relationship to the programs of general-equilibrium theory and econometrics, whose modern incarnations both date from exactly the same period in the 1930s.
Keywords: B2; B22; E1; 330; microfoundations of macroeconomics; general equilibrium; aggregation; representative agent; fixed-price models; econometric models